2017
DOI: 10.1097/tp.0000000000001689
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Waitlist and Posttransplantation Outcomes in Liver Transplant Registrants and Recipients Aged 18 to 24 Years

Abstract: Background We evaluated liver transplantation waitlist and posttransplantation outcomes in 18–24 year olds compared to both younger (0–17 year old) and older (25–34 year old) registrants and recipients. Methods Utilizing national data from the United Network for Organ Sharing, competing risk, Cox regression and Kaplan-Meier analyses were performed on first-time liver transplant registrants (n=13,979) and recipients (n=8,718) ages 0–34 years old between 2002 to 2015. Results Among nonStatus 1A registrants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Consistent with studies demonstrating the impact of socioeconomic burden on pretransplantation management and referral, ( 8,17‐19 ) we found that higher levels of education and employment were protective against waitlist mortality and clinical deterioration. These findings may be explained in part by greater compliance with medical recommendations, access to care prior to LT, or disease severity.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with studies demonstrating the impact of socioeconomic burden on pretransplantation management and referral, ( 8,17‐19 ) we found that higher levels of education and employment were protective against waitlist mortality and clinical deterioration. These findings may be explained in part by greater compliance with medical recommendations, access to care prior to LT, or disease severity.…”
Section: Discussionsupporting
confidence: 90%
“…Our observation of worse patient and graft outcomes in children transplanted at progressively older ages compared to those transplanted at age <5 years is not a new observation. Dharnidharka et al, Ebel et al, and Sagar et al have all noted this same trend of teenagers being most at risk for death and graft loss. This is not entirely unexpected, as transplantation during adolescence has previously been strongly associated with non‐adherence; adolescents are reported to have a rate of immunosuppression non‐adherence twice as high as younger cohorts; moreover, when patients begin self‐managing their condition, non‐adherence may be even greater .…”
Section: Discussionmentioning
confidence: 76%
“…De novo autoimmune hepatitis and recurrent hepatitis were the only hepatitides reported in our registry report accounting for a total of 29 reports of graft loss in the 2000-2014 era ( Figure 5). 16,20,21 have all noted this same trend of teenagers being most at risk for death and graft loss. This is not entirely unexpected, as transplantation during adolescence has previously been strongly associated with non-adherence 22,23 ; adolescents are reported to have a rate of immunosuppression non-adherence twice as high as younger cohorts; moreover, when patients begin self-managing their condition, non-adherence may be even greater.…”
Section: Discussionmentioning
confidence: 81%
“…Adolescent and young adult solid organ transplant recipients have the greatest incidence of graft loss among age groups, likely due to poor medication adherence, so frequent DSA monitoring may be necessary for this high-risk group. [34][35][36][37][38][39] There are several limitations to the present study. First, this was a small, single-center, retrospective review without controls.…”
Section: Discussionmentioning
confidence: 92%
“…DSA monitoring is beneficial for early detection of dnDSA, as well as long‐term follow‐up of AMR treatment efficacy. Adolescent and young adult solid organ transplant recipients have the greatest incidence of graft loss among age groups, likely due to poor medication adherence, so frequent DSA monitoring may be necessary for this high‐risk group …”
Section: Discussionmentioning
confidence: 99%